KANDUNGAN SENYAWA STEROID-ALKALOID PADA EKSTRAK n-HEKSANA DAUN BERINGIN (Ficus benjamina L) - Sukadana, I Made (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 2 Juli 2011, 2012)
Isolation of steroid-alkaloid compounds from Banyan leaf (Ficus benjamina L.) has been carried out. As much as 27.13 g of concentrated ethanol extract was resulted from 1.0 kg dried powders of Banyan leaf that was macerated using ethanol as a solvent. Further, this extract was partitioned with n-hexane to obtain 11.39 g concentrated extract of n-hexane. Ethanol extract was dissolved in ethanol-water (7:3), then was evaporated leaving water extract. Futhermore these water extract was partitioned with chloroform to obtain 0.7 g concentrated chloroform extract which was dark green and 2.21 g concentrated water extract which was green. Separations of n-hexane extract containing steroids using column chromatography (stationary phase : silica gel 60 and mobile phase : chloroform-ethylacetate (4:1)) resulted in fourteen fractions with F8 fraction being the most positive toward Liebermann-Burchard reagent, but this fraction contains at least in five components. Purification of the F8 fraction using TLC preparative resulted in six fractions (F8.1, F8.2, F8.3, F8.4, and F8.5) with F8.1 fraction being the most active steroid. The infrared spectrophotometer analysis suggested that the isolate (F8.1 fraction) was a steroid-alkaloid compound having functional groups including O-H stretching at 3448.72 cm-1 that was supported by one band C-OH streching at 1381.03 cm-1, the band of C-H aldehyde group at 2924.09 and 2854.65 cm-1 and the carbonyl group C=O of aldehyde at 1735.9 cm-1. Absorption at 2337.72 cm-1 indicated C?N stretching which was supported by N-H aliphatic and C-N aliphatic groups at 1172.72 and 1111.00 cm-1 respectively. The other groups were C=C aliphatic (1558.48 cm-1), C-H aliphatic bending (1458.18 cm-1), and C-O-C stretching (1257.59 cm-1). The gas chromatogram and mass spectra showed an isomer compound with Mr of 393 and molecular formula of C24H27O4N which was an alkaloide.
Keywords: Ficus benjamina L., steroid, alkaloide, isolation, identification